Sulfur defect rich Mo-Ni3S2 QDs assisted by O–CO chemical bonding for an efficient electrocatalytic overall water splitting. Issue 13 (29th March 2021) - Chen, Honglei; Yu, Zebin; Jiang, Ronghua; Huang, Jun; Hou, Yanping; Zhang, Yongqing; Zhu, Hongxiang; Wang, Bing; Wang, Mi; Tang, Wenjun
Abstract : Developing earth-abundant and highly efficient electrocatalysts is critical for further development of a system. Abstract : Developing earth-abundant and highly efficient electrocatalysts is critical for further development of a system. The metal (M) doping strategy and inorganic/organic composite are two common strategies to improve the performance of electrocatalysts for overall water splitting (OWS). In this paper, two strategies are subtly used to prepare Mo-Ni3 S2 quantum dots (QDs) with rich sulfur defects through Mo n + doping Ni3 S2 and introduction of trisodium citrate by a two-step hydrothermal reaction. Results show that high sulfur defects can be controllably prepared as the lattice mismatch and active sites can be efficiently increased via Mo n + doping. Moreover, the introduction of trisodium citrate with carboxyl functional groups not only enhances the degree of sulfur defects around the metal center, changes the morphology of sulfide to distribute the active centers evenly, but also endow the metal center with strong valence changing ability with organic characteristics. The in situ Raman study reveals that O–CO promotes the formation of the real active site M-OOH by the way of self-sacrifice during the OER process. Mo-Ni3 S2 QDelectrocatalyst shows excellent performance in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), achieving a current density of 10 mA cm −2 at the overpotentials of 115 mV and 222 mV with very good chemical stability, superior than that of most of the reported materials. The OWS reaction can provide a current density of 10 mA cm −2 and 50 mA cm −2, which only needs 1.53 V and 1.74 V with excellent industrial application prospects.